Design and Modelling the System for Ablution Recycle Water - Zakaria, Nadzmi Zarith (Universiti Teknologi PETRONAS, 2020)
Recycling and reuse of ablution water and rainwater has become one of the alternatives especially for countries that often have problems in terms of water supply. Recycled water is used for the purpose of activities such as agricultural and landscape irrigation and irrigation in public parks, toilet flushing which has been practiced abroad. This study proposes the development of a treatment system aimed at collecting and filtering ablution water and rainwater. The proposed system contains several filters aimed at filtering the resulting sands or impurities along with ablution water and rainwater. In this paper, we will be mainly focusing on the creating of the water pump and the water system.